Neuroimmunological Aspects in Glaucoma Neuroimmunologische Auffälligkeiten beim Glaukom - Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2021)
Glaucoma pathogenesis hast still to be elucidated. Next to its main risk factor, an increased intraocular pressure, an e.g. altered biomechanics of the lamina cribrosa, oxidative stress-mediated changes and glutatmate toxicity are involved in this multifactorial pathophysiology. Recent experimental studies and clinical findings suggest an involvement of the immune system in glaucoma. This review will give an overview of the different immunologic aspects being involved in glaucoma pathogenesis.
CRIS-Team Scopus Importer:2021-03-05
Keywords: autoantibody; glaucoma; immune system